Pengaruh Lokasi Ketebalan Maksimum Airfoil Simetris Terhadap Koefisien Angkat Aerodinamisnya - Nurcahyadi, Teddy; Sudarja, Sudarja (Jurnal Semesta Teknika, 2008)
Airfoil performance data is regarded as highly valuable data in its wide area of application since it will help the designer, for examples; to predict the influence of rear spoiler mounting to the maneuverability and top speed of racing car, the thrust and fuel consumption needed for an aircraft to take off and cruise, or the power delivered by a wind turbine rotor at certain wind speed. The performance of airfoil, which is measured with its lift and drag coefficient, is greatly affected by its geometry and operating condition. The influence of various geometric and operational parameters to the airfoil performance is needed to be studied experimentally and the airfoil performance data obtained can be added to enrich the airfoil performance data base. The experiment was done by testing airfoil models by lift force direct measurements in a sub-sonic wind tunnel.Â The type of airfoil used in this experiment is the symmetric airfoil with maximum thickness location as the geometric parameter and angle of attack with wind speed as the operational parameter being investigated for their influence to the lift and drag coefficient. The maximum thickness location was varied in 30%, 40%, and 50% of chord length measured from leading edge. The angle of attack was varied from 0o to 20o with 4o increments. The wind speed was varied from 10 m/s to 20 m/s with 2 m/s increments.Â Parameters being measured were the free stream velocity, and the lift force. The result of the research shows that the best airfoil performance with lift coefficient 3,16 is achieved by the airfoil that has maximum thickness location in 40% of its chord length measured from its leading edge and operates at 20o angle of attack and 8,9Â m/s free stream velocity.